Succession of states in respect of state responsibility: towards yet another Vienna Convention - Kaplane, Anastasija (Riga Graduate School of Law, 2020)
The end of the twentieth century was characterised by a series of state dissolution cases, such as the breakup of Czechoslovakia, the Socialist Federalist Republic of Yugoslavia, and the Soviet Union. In that context, the rules on state succession regained relevance, with the issue of state succession in respect of international responsibility becoming central. The topic first attracted the attention of the academic community and subsequently was chosen by the International Law Commission for study and codification. The present article examines the historical evolution of the rules on the succession of states, providing a review of case law where the Court referred to the concept of state succession to international responsibility, expressly or by implication. The author analyses the wording of the proposed Draft Articles and attempts to establish whether and how the principles of automatic succession and non-succession apply in different circumstances based on the newly developed provisions. The purpose of the study is to identify the advantages and disadvantages of the proposed Draft Articles as well as to discuss whether there is a need for codification of such rules.
Keywords: State succession; State responsibility; International Law Commission